THE USE OF BUBBLE MAP TO IMPROVE STUDENTS’ ADJECTIVE VOCABULARY MASTER THROUGH DESCRIPTIVE TEXT WRITING - Mustika, Yeni; Sudarsono, Sudarsono; Sada, Clarry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was aimed to improve students’ adjective vocabulary by using bubble map through descriptive text writing to Class B students of Year-7 in MTs Darussalam Sengkubang Academic Year 2017 / 2018 membership 22 students. The research question was how well the use of bubble map included word mapping and write simple sentences improve students’ adjective vocabulary mastery. This research was a classroom action research with three cycles. Each cycle consisted of planning, acting, observing, and reflecting. Field note, observation checklist, interview, and individual test were used as the tools to collect the data. The finding of this research was that there was significant improvement from cycle to cycle. Through the implementation of bubble map to teach adjective vocabulary improved qualitatively and quantitatively. By using bubble map through descriptive text writing, the students developed their critical thinking in finding the new adjective vocabulary by creating and exploring their ideas into a map.Keywords: Adjective Vocabulary, Bubble map, Classroom Action Research, Writing Descriptive Text.